Phosphorus containing carbon (submicron) fibers as efficient acid catalysts - García-Mateos, Francisco José; Ruiz-Rosas, Ramiro Rafael; Rosas-Martínez, Juana María; Rodríguez-Mirasol, José; Cordero-Alcántara, Tomás (Elsevier, 2022)
Porous carbon fibers catalysts have been prepared by electrospinning of Alcell lignin, a green carbon precursor, which could be obtained as by-product in wood-to-ethanol biorefineries. The addition of H3PO4, a well-known chemical activation agent, to the electrospinning lignin solutions, at different mass ratios and the use of different carbonization temperatures, between 500 and 1600 ºC, were analyzed in order to obtain carbon fibers with a large variety of porosity and chemical surface properties. Isopropanol decomposition was used as a catalytic test. Phosphorus-containing carbon fibers showed acid character and high catalytic activity, achieving propylene selectivity of 100 % under inert atmosphere. However, the use of air atmosphere increases the isopropanol conversion but produces the formation of acetone, via oxidative dehydrogenation, at low temperatures ( 20%). Ethanol and methanol decomposition were also evaluated in air stream for the most active phosphorus-containing carbon catalyst, showing improved alcohol conversions with minimal gasification of the carbon fibers. These results confirmed that phosphorus-containing carbon fibers prepared by electrospinning of lignin solutions were excellent catalysts for alcohol dehydration reactions.
https://openpolicyfinder.jisc.ac.uk/id/publication/16707
CTQ2015-68654-R RTI2018 097555-B-100 PTA2015-11464-I
Keywords: Fibras de carbono; Hilatura; H3PO4; Alcohol dehydration; Activated carbon fibers; Catalyst; Electrospinning